Comparative study of Object Recognition Algorithms - Jaiswal, R.S.; Sarode, M.V. (International Journal of Engineering and Technology, 2018)
The world we live in is full of enormous masses of digital visual information. This enormousÂ amount of digital visual information motivates us to develop robust and efficient object recognition technique. Most of the work reported in this paper focuses focus light uponÂ efficient techniques that can be used for recognition of object and its applications.Â Here in this paper, various techniques for object recognition in an image are discussed.